Bichos bons de se comer, bichos bons de se ter : apropriações da fauna na América Portuguesa Quinhentista - Oliveira, Natalia Fernanda Ramos de (2016)
The present conditions of fauna and flora in the countries once colonized by the Europeans are mainly the result of the anthropic action undertaken in the localities, according to their economic or ideological importance. As the distribution of all living beings takes place in space-time, a historical rescue was made of the processes carried out by the settlers, who are mainly responsible for the current situation of the Brazilian fauna and flora, without neglecting the societies that already resided in Brazil before the arrival of the first Europeans and which caused significant environmental impacts. The sixteenth century was a period of foundation for Brazil and its nature; the environment is not considered a historical agent in the process of forming any culture, although it is the most explored. In this research, nature was placed as the main character, acting even when dominated. And it was still in the period of the Great Navigations that certain truths hitherto unquestionable have come to be questioned, especially regarding the place of the human being in nature. New sensitivities arise in relation to animals, plants and the landscape. The research exposes the presuppositions, articulated or not, that based the established relations of the human beings with the animals in Brazil from the arrival of the Europeans. Guided by the questioning of how the first settlers and Portuguese travelers related to animals in the first century of colonization in Brazil and which were the most used animals for certain functions, we carried out the investigation based on the historical context of the XVI and, possibly, XVII centuries, and how these relations were decisive for the current situation in which the Brazilian fauna is found. The research focused specifically on the citations and references to animals in Brazil in sixteenth century narrative documents such as Gabriel de Souza, Jean de Léry, André Thévet, Pero de Magalhães Gândavo, George Marcgrave among others. The general objective of the research is to recover the written works about Brazil, by European chroniclers and explorers, in the 16th century, in order to characterize the foundations on which the ideas about nature in the tropical world were based, what role the animals played at the beginning of colonization and how this sixteenth-century vision influenced man's relationship with nature, specifically with brazilian fauna. Was it questioned how animals were defined according to their utility and, in particular, became food in such a troubled period between survival and exchange cultures? The philosophical conjuncture of the period was contextualized to understand the actions undertaken by the colonizers and their exploratory chroniclers. It took into account also the factors that encouraged the first settlers to carry out such an undertaking with such a diverse nature. The foundations of what, from the eighteenth and nineteenth centuries, might be called utilitarianism, can be found in the relationship established from this much sought after utility of nature by the colonizers. From the first century of occupation and settlement, bovine cattle were brought from Europe, as can be seen from the references to "cow pens". And although the colonizer has experienced from the flesh of many wild animals, among mammals and birds and eventually reptiles and fish, native animals were not effectively incorporated into the colonizer's menu or the European menu except for some marine specimens that will be treated here.